2012
DOI: 10.1002/asna.201211669
|View full text |Cite
|
Sign up to set email alerts
|

Charge‐exchange emission in the starburst galaxies M82 and NGC3256

Abstract: Charge-exchange (CE) emission produces features which are detectable with the current X-ray instrumentation in the brightest near galaxies. We describe these aspects in the observed X-ray spectra of the star forming galaxies M82 and NGC 3256, from the Suzaku and XMM-Newton telescopes. Emission from both ions (O, C) and neutrals (Mg, Si) is recognised. We also describe how microcalorimeter instrumentation on future missions will improve CE observations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Some of these lines have also been found in extragalactic star-forming environments (starburst galaxies), and taken as evidence of charge exchange (CX) processes, associated with the cold gas and/or the cold gust, at the hot-cold interface. For instance, Ranalli et al (2008) and Ranalli (2012) found evidence for CX lines in M82 both from ions (O, C) and from neutrals (Mg, Si). In particular, Ranalli et al note that their lines could be caused by CX in highly-excited O VIII ions (0.78 keV) and neutral Mg (1.254 keV), and that this might indicate the presence of, e.g., olivine grains in the cold clouds of M82.…”
Section: The Carina Nebula: First Evidence For Charge Exchange In a Smentioning
confidence: 99%
“…Some of these lines have also been found in extragalactic star-forming environments (starburst galaxies), and taken as evidence of charge exchange (CX) processes, associated with the cold gas and/or the cold gust, at the hot-cold interface. For instance, Ranalli et al (2008) and Ranalli (2012) found evidence for CX lines in M82 both from ions (O, C) and from neutrals (Mg, Si). In particular, Ranalli et al note that their lines could be caused by CX in highly-excited O VIII ions (0.78 keV) and neutral Mg (1.254 keV), and that this might indicate the presence of, e.g., olivine grains in the cold clouds of M82.…”
Section: The Carina Nebula: First Evidence For Charge Exchange In a Smentioning
confidence: 99%